(untitled) (Journal of Health, Technology and Science (JHTS), 2025)
This study aims to identify the marketing strategies implemented by Multazam Hospital Gorontalo to increase inpatient visits, analyze the application of these strategies, and determine the internal and external factors influencing their effectiveness. The research employed a qualitative approach through in-depth interviews with hospital management and relevant staff. The results show that Multazam Hospital’s marketing strategy integrates the use of social media (Facebook and Instagram), community outreach activities, and external partnerships with government institutions, banks, BPJS, and private organizations. The implementation of marketing strategies focuses not only on external promotion but also on improving internal service quality, including hospitality, service speed, the professionalism of medical staff, and the comfort of inpatient facilities. Internal factors influencing the success of marketing strategies include medical human resource competence, service quality, and limitations in IT and marketing teams. External factors consist of BPJS referral system regulations, competition with other hospitals, and opportunities for collaboration with various stakeholders